Corpo, beleza e auto-objetificação feminina - Loureiro, Carolina Piazzarollo (2014)
Self-objectification consists in the internalization of a third-perspective observer over one’s own body, occurring as consequence of the recurring experiences of sexual objectification of the individual. It leads to preoccupation with physical appearance over body states and physical skills, being manifested by constant body surveillance, which can lead to various consequences that impact one’s health and well-being. This thesis aimed to explore the body experiences of Brazilian women, investigating their conceptions of beauty and experiences of self-objectification. For this, two studies were conducted. The first study used evocations to investigate the social representations of "beautiful woman", "beautiful female body" and "female body in the media" of 185 women from across Brazil, with ages ranging between 18 and 60 years (M = 25.97, SD = 6.98), who responded voluntarily and anonymously to an online questionnaire. The results suggested the participants’ perception and internalization of a beauty standard focused on thinness and defined muscles, and showed that the female body presented in the media generated a significant number of negative feelings and thoughts among the participants. The second study used the theoretical framework of the Theory of Objectification to investigate the relationship between sexually objectifying media, internalization of sociocultural standards of beauty, self-objectification, body shame, self-esteem and body esteem among 340 university students of the state of Espírito Santo, Brazil, aged between 18 and 25 years. Furthermore, it aimed to translate and validate the Objectified Body Consciousness Scale and the female version of the Body Esteem Scale for use in Brazil. Data collection was conducted in person and included a questionnaire with demographic and media consumption questions (TV, magazines and internet), the Objectified Body Consciousness Scale, the Female Scale of Body Internalization, the Rosenberg Self-Esteem Scale and the female version of the Body Esteem Scale. Additionally, the participants were divided randomly between the control condition, where they were presented to neutral images, or one of four experimental conditions, where they were primed with pictures of skinny models or plus size models before or after the scales. The results indicate that the Objectified Body Consciousness Scale and the female version of the Body Esteem Scale have been validated for use with Brazilian female undergraduates, however it is necessary to review the translation of the excluded items from Objectified Body Consciousness Scale before it can be considered fully validated. Furthermore, it was shown that sexually objectifying media images only influenced female self-objectification when they were in accordance with the standard of beauty; and that self-esteem may be an important variable to be worked into future strategies for prevention and intervention against self-objectification. Despite several limitations of this work, it brings important contributions to the body related research while inaugurating the study of self-objectification in Brazil, as well as demonstrating empirically the importance of public policies aimed at reducing sexual objectification of women and the promotion of body diversity acceptance.